The Tri-N Model of Ki Hajar Dewantara in Life Skills Education for Women's Empowerment - Monica Widyaswari; Dedi Kuswandi; Agus Wedi; Dyah Permata Sari; Agustin Hanivia Cindy; Adjie Pradana Wibowo (Jurnal Pemberdayaan Masyarakat, 2026)
The Tri-N Model of Ki Hajar Dewantara emphasizes a progressive learning process that moves beyond imitation toward creativity and productivity in life skills education. However, its application in women's empowerment contexts requires further examination to ensure that students can critically process and transform the knowledge they acquire. This study aims to analyze the relevance and implementation of the Tri-N Model in life skills education for women's empowerment. A qualitative approach was employed in this study, conducted in Kediren Village, Magetan, East Java. Informants were selected purposively, consisting of facilitators and women students. Data were collected through observation, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the Tri-N Model is implemented through three stages—niteni (observing), nirokke (imitating), and nambahi (modifying)—which support both skill acquisition and creative development. In batik-making activities, the model enhances technical competence, strengthens cultural understanding, and contributes to women's empowerment by increasing self-confidence, independence, and economic capacity. This study suggests that the Tri-N Model is a relevant, culturally grounded pedagogical approach for life skills education, with the potential to support sustainable empowerment, though further research is needed to examine its long-term impact.